La planeación estratégica para la viabilidad empresarial de Emapa San Martin S.A. - Zegarra Chung, Juan (2009)
This research work entitled "The Strategic Planning for Business Feasibility EMAPA SAN MARTIN S.A., proposes the practice of strategic planning as an alternative tool for business management model that enables the business viability of EMAPA SAN MARTIN.S.A. In this research work is diagnosed and described the proposed model, labor obtained through the collection of data both within the company and outside of it. It has done the analysis and interpretation of management indicators and determining their business viability. From the results obtained confirms the general null hypothesis EMAPA SAN MARTIN SA, is not viable in business terms is not practiced strategic planning as a management model for business management.